Using a choice experiment to estimate farmers' valuation of agrobiodiversity on Hungarian small farms - Birol, Ekin; Smale, Melinda; Gyovai, Agnes (Springer, 2006)
Agrobiodiversity is a crucial environmental resource. Much of the agrobiodiversity remaining in situ today is found on the semi-subsistence farms of poorer countries and the small-scale farms or home gardens of more industrialised nations. The traditional farms of Hungary are an example. Labelled ''home gardens'' as a reflection of their institutional identity during the collectivisation period, they are micro-agroecosystems that provide important functions such as food security and diet quality. This paper applies the choice experiment method to estimate the private benefits farmers derive from four components of the agrobiodiversity found in Hungarian home gardens: richness of crop varieties and fruit trees; crop landraces; integrated crop and livestock production; and soil micro-organism diversity. The analysis is based on primary data collected in three environmentally sensitive areas where pilot agri-environmental programmes have been initiated as part of the Hungarian National Rural Development Plan. Findings demonstrate variation in the private values of home gardens and their attributes across households and regions, contributing to understanding the potential role of home gardens in these agri-environmental schemes. This study has implications for sustaining agrobiodiversity in transitional economies.